Evaluating The Flexural Strength and Charpy Impact Strength Of CAD/CAM And Compressed Molded PMMA Dentures: An In Vitro Study - Asma Abdeewi; Gazia Elbakosh; Asam Aljiwiw; Tawfik Ajaal (AlQalam Journal of Medical and Applied Sciences, 2024)
PMMA (Polymethyl methacrylate) is a wide range of polymers are commonly used for various applications in prosthodontics. And the embedding of tooth specimens for research purposes. The unique properties of PMMA, such as its low density, aesthetics, cost-effectiveness, ease of manipulation, and tailorable physical and mechanical properties, make it a suitable and popular biomaterial for these dental applications. These complete dentures can be manufactured using two techniques: (i) conventional compression molding (CCM) technique and (ii) CAD/CAM technology. The objective of this study was to evaluate the mechanical properties of CAD/CAM PMMA denture compared to compressed molded PMMA, manufactured using the CCM technique and CAD/CAM technology. The study consisted of twenty samples, divided into two groups based on their manufacturing technique (conventional and CAD/CAM), with five samples assigned to each test. The mechanical properties of the samples were tested using flexural strength, and Charpy impact strength tests after immersing the samples in artificial saliva at 37°C for one week. The results showed that using different manufacturing techniques for PMMA CDs leads to differences in measured characteristics that affect their suitability as the only available treatment for edentulous patients. However, a statistical analysis using SSPS tools showed that the differences are not significant between the CCM technique and CAD/CAM technology. Despite the lack of statistical significance, The PMMA CDs manufactured using the CAD/CAM technology route are recommended due to their better mechanical resistance properties.